EFEKTIVITAS PROSES PEMBELAJARAN MATA KULIAH MANAJEMEN KEUANGAN UNTUK KEPARIWISATAAN (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
Financial literacy is an important managerial skill for every student. Ciputra University with its main value of entrepreneurship also prioritizes financial literacy as an ability that must be mastered by students and graduates. Therefore, learning Financial Management at the Tourism Study Program, Ciputra University Surabaya is structured so that it can implement the practical use of accounting and finance learning in the tourism industry. This study aims to determine the effectiveness of the Financial Management learning process for Tourism at Ciputra University Surabaya. The research method was carried out through limited trials on the subject of Financial Management for Tourism by adapting the classroom action research model by Kemmis and McTaggart which consisted of four stages, namely planning, action, observation, and reflection. . The learning process is divided into two cycles, and in each cycle evaluation and improvement efforts are made to improve the learning process in the next cycle. The results showed that the learning process in the Financial Management for Tourism course had reached the specified learning achievement target. The practical implementation of financial management which is manifested in the form of business plan design has a positive effect on increasing the financial literacy skills of undergraduate students of the Tourism Studies Program class A at Ciputra University, Surabaya. Student learning outcomes increased as indicated by the percentage of student learning completeness reaching 82.35% in the Financial Management for Tourism course